Poststructural Policy Analysis - Bacchi, Carol. author. aut Link
IX, 178 p. 1 illus.
Keywords: This book offers a distinctive approach to policy analysis and a refreshing and politically engaged way of thinking about policy. It clearly articulates a Foucault-influenced poststructural perspective on policy and policy analysis for researchers, students and policy makers. As a "guide to practice", the book introduces a critical analytical approach to policy analysis called ‘What’s the Problem Represented to be?’ (WPR). Instead of treating policy as simply the government’s best efforts to address problems, this analytic strategy highlights how policies produce ‘problems’ as particular sorts of problem and how governing takes place through these problematisations. First published in 2016, the book describes the conceptual and theoretical underpinnings of the WPR approach to policy analysis in a detailed and accessible manner. It features examples of application of the approach with topics as diverse as obesity, economic policy, migration, drug and alcohol policy, and gender equality. In this second edition, the authors centralise a complementary analytic strategy for poststructural policy analysis—poststructural interview analysis (PIA). This edition integrates this material as a new chapter which sets out PIA as a novel approach to poststructural interview analysis and includes examples of PIA applications. The new chapter provides excellent guidance to undertake interview analysis in a manner congruent with the poststructural precepts set out in the book. Carol Bacchi is Professor Emerita of Politics at the University of Adelaide, Australia. Her work over the past forty years has encouraged rethinking of taken-for-granted truths about women’s history, equality policy and public policy generally. Major publications include Same Difference: Feminism and Sexual Difference (1990/2024), Women, Policy and Politics: The Construction of Policy Problems (1999), The Politics of Affirmative Action: 'Women', Equality & Category Politics (1996) and Analysing Policy: What’s the Problem Represented to Be? (2009). Susan Goodwin is Professor of Policy Studies at the University of Sydney, Australia. Her research focuses on social policy and policy processes, and she is involved in critical policy analysis with organisations at local, national and international levels. Her books include Working Across Difference: Social Work, Social Policy and Social Justice (2019), Markets, Rights and Power in Australian Social Policy (2015), Schools, Communities and Social Inclusion (2011) and Social Policy for Social Change (2010). .